Crises and The Development of Economic Institutions: Some Microeconomic Evidence - Rajan, Raghuram; Ramcharan, Rodney (American Economic Review, 2016)
This paper studies the long run effects of financial crises using new bank and town level data from around the Great Depression. We find evidence that banking markets became much more concentrated in areas that experienced a greater initial collapse in the local banking system. There is also evidence that financial regulation after the Great Depression, and in particular limits on bank branching, may have helped to render the effects of the initial collapse persistent. All of this suggests a reason why post-crisis financial regulation, while potentially reducing financial instability, might also have longer run real consequences.